High‐resolution analysis of copy number variants in adults with simple‐to‐moderate congenital heart disease. Issue 12 (24th September 2013) - Zhao, Wei; Niu, Guannan; Shen, Botao; Zheng, Yang; Gong, Fangchao; Wang, Xianfu; Lee, Jiyun; Mulvihill, John J.; Chen, Xiaohui; Li, Shibo
Abstract As patients with congenital heart disease (CHD) increasingly survive to childbearing age, it becomes important to understand the genetic origins of CHD. In children, CHD is frequently caused by chromosomal imbalances. We searched for submicroscopic imbalances in adults with CHD focusing on simple‐to‐moderate phenotypes, without associated dysmorphic features, a group not previously examined. A total of 100 Han Chinese adults with a diverse range of isolated CHD and 65 ethnically matched controls were screened using whole‐genome array comparative genomic hybridization. Forty‐five large (>100 kb) rare copy number variants (CNVs) were identified in 36/100 patients. These variants were not listed in the Database of Genomic Variants nor found in controls. In three of these genomic imbalances (22q11.2, 18q23, 3q21.3), genes that play an important role in cardiac development were implicated, including CRKL, NFATC1, PLXNA1, the latter has not been associated with human CHD before. This study detected a 0.7 Mb 22q11.2 deletion, which marginally overlapped the common 3 Mb 22q11.2 deletion, in one patient with a perimembranous ventricular septal defect without any extracardiac manifestation. Furthermore, we detected a novel inherited aberration dup (16q23.1). Although a causal relationship with CHD remains to be established, this CNVs profile provides a spectrum of genomic imbalances in this condition, and improves the CNV‐phenotype correlations. © 2013 Wiley Periodicals, Inc.